2022
DOI: 10.1155/2022/1603273
|View full text |Cite
|
Sign up to set email alerts
|

U-Net: A Smart Application with Multidimensional Attention Network for Remote Sensing Images

Abstract: Building segmentation is an important step in urban planning and development. In this work, we propose a new deep learning model, namely Multidimension Attention U-Net (MDAU-Net), to accurately segment building pixels and nonbuilding pixels in remote sensing images. Furthermore, we introduce a novel Multidimension Modified Efficient Channel Attention (MD-MECA) model to enhance the network discriminative ability through considering the interdependence between feature maps. Through deepening the U-Net model to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Through collecting and sorting the rainfall data of the study area in the past 20 years, the Kriging interpolation is used to generate the thematic map of the annual rainfall in the study area (refer to Figure 3(f) for details). Furthermore, vegetation coverage is an impact factor of the landslide, and the thematic map of the vegetation coverage in the study area is obtained through using the ENVI 5.3 software [ 21 ]. In this study, the vegetation coverage is divided into five different categories (as shown in Figure 3(g) ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through collecting and sorting the rainfall data of the study area in the past 20 years, the Kriging interpolation is used to generate the thematic map of the annual rainfall in the study area (refer to Figure 3(f) for details). Furthermore, vegetation coverage is an impact factor of the landslide, and the thematic map of the vegetation coverage in the study area is obtained through using the ENVI 5.3 software [ 21 ]. In this study, the vegetation coverage is divided into five different categories (as shown in Figure 3(g) ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, vegetation coverage is an impact factor of the landslide, and the thematic map of the vegetation coverage in the study area is obtained through using the ENVI 5.3 software [ 21 ]. In this study, the vegetation coverage is divided into five different categories (as shown in Figure 3(g) ).…”
Section: Methodsmentioning
confidence: 99%
“…Methods. We implemented three different machine learning algorithms, that is, CNN, RNN, and U-net [33], where the training happens on a cloud and prediction at the edge. e U-net method is implemented along with the attention mechanism.…”
Section: Results Of the Machine Learning And Aggregationmentioning
confidence: 99%
“…Moreover, the F1 score is the harmonic average of recall rate and precisions (accuracy). Finally, the IoU is the crossing of pixels labelled as building in the ground truths and anticipated outcomes and subsequently divided by the union of pixels labelled as building in the ground truths and forecasted outcomes [8].…”
Section: Discussion and Model Accuracymentioning
confidence: 99%
“…is should be noted that, due to (i) no availability of duplicate entries and (ii) small size of the dataset, we do not use any aggregation technique in this work. Largely, the well-known Euclidean distance equation is used to identify whether two particular collected data points (through sensors) belong to either the same region or two different regions, which is used for data aggregation purpose [8,9]. e processed data is then moved to the cloud for long-term storage.…”
Section: Evaluation Of Debris Flow Susceptibility Based On Random For...mentioning
confidence: 99%